Individual-based Modeling of Genome Evolution in Haplodiploid Organisms. (2nd May 2022) - Pracana, Rodrigo; Burns, Richard; Hammond, Robert L.; Haller, Benjamin C.; Wurm, Yannick
Abstract: Ants, bees, wasps, bark beetles, and other species have haploid males and diploid females. Although such haplodiploid species play key ecological roles and are threatened by environmental changes, no general framework exists for simulating their genetic evolution. Here, we use the SLiM simulation environment to build a novel model for individual-based forward simulation of genetic evolution in haplodiploids. We compare the fates of adaptive and deleterious mutations and find that selection on recessive mutations is more effective in haplodiploids than in diploids. Our open-source model will foster an understanding of the evolution of sociality and how ecologically important haplodiploid species may respond to changing environments.